Left Atrial Thrombus Resolution Using Unfractionated Heparin and Warfarin in a Patient with Mitral Stenosis - Zainuddin Zainuddin; Endang Ratnaningsiah; Andika Rizki Lubis; Sebastian Andi Manurung; Tike Hari Pratikto; Amiliana Mardiani Soesanto (Jurnal Kardiologi Indonesia, 2019)
Abstract Background: Though the use of Low Molecular Weight Heparin (LMWH) in general is preferred due to its convenient and eliminates the need for activated Partial Thromboplastin Time ( aPTT) monitoring but Unfractionated Heparin (UFH) is still widely used in clinical setting due to its availability and low price. Besides UFH, the use of oral anticoagulant therapy with warfarin, has been the standard therapy for the prevention of thromboembolism in patients with AF. Our aim is to report a case of the resolution of left atrial thrombus in a patient with mitral stenosis. Case Illustration: A Case report of a female patient aged 54 years who admitted with a sudden neurological deficits and mitral stenosis with atrial fibrillation. Transthoracal Echocardiography (TTE) showed mobile thrombus which moved and obstructed the mitral valve during diastolic phase. Unfractionated heparin (UFH) was administered 3000 unit bolus intravenously and maintained with 600 unit per hour with the combination of warfarin 2 mg for five days. TTE evaluation showed the resolution of LA thrombus. Conclusion : The administration of the combination of UFH and warfarin had successfully caused resolution of the LA thrombus and prevented the patient from surgical intervention. This case report indicated that Unfractionated Heparin and Warfarin were still the treatments option in LA thrombus patients with mitral stenosis and atrial fibrillation. Key words :Left atrial thrombus, unfractionated heparin, thrombus resolution